Pre-dentistry academic performance and dexterity examination as predictors of pre clinical performance in UP College of Dentistry - Crisostomo, Pamela Cristina P.
The study was done on 122 subjects to determine the predictive value of the pre-dentistry grades and the carving and perspective drawing components, as well as the total dexterity evaluation conducted om entering UPCD proper freshmen. Their admission grades were correlated and regressed against four lecture and laboratory course in the preclinical years namely: Oral Anatomy, Restorative Dentistry 12, Restorative Dentistry 21, and Fixed Partial Prosthodontics 21. Non-grade attributes were not part of the study. The author concludes that: (1) the pre-dentistry academic performance had strong positive correlations with the first and second year lecture grades and weak to moderate significant correlations with the first year laboratory grades; (2) the carving average and dexterity evaluation have weak moderate correlation with the laboratory performance as well as with the first year lecture grades; (3) correlation values were higher in the first year than the second year subjects; (4) the weighted average of core subjects significantly predicts first year lecture grades, while the GWA predicts sophomore lecture subjects; and (5) the dexterity evaluation predicts the laboratory grades in Oral Anatomy, Restorative 12 and 21, while the perspective drawing subtest significantly predicts the grade in FPD lab.